Rivalitas Strategi Penggunaan Sarana dan Prasarana Politik pada Pilkada Kota Parepare Tahun 2013 - Andi Fitri Rahmadany (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Local election in Parepare City which won by Taufan Pawe-Faisal Andi Sapada (TP-FAS) in one round is caused by several strategies that is not used by their competitors. Start from political support, financial support, national figure support, creativity and innovation, campaign methods, and also NGO’s support. There are several strategies that are used by other, but it is not suitable with local people structure. TP-FAS has won to indicate what people want and how to make it usefull for them.